PENERAPAN STRATEGI SURVEY QUESTION READING RECITE REVIEW (SQ3R) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA - Khaerunnisa, Khaerunnisa; Salam, Rosdiah; Astuti, Uli (Universitas Negeri Makassar, 2018)
This study aims to describe the application of learning strategy of SQ3R to improve reading comprehension ability of the fourte grade student of SDN Mapala Kec. Rappocini Makassar. Type of this research is class room action research wich overwhelm planning step, action, observation and reflection. This research is focus on student n teacher. Result of the research shows that teacherâ€™s teaching activity in cycle is in category cukup while in cycle II is in category baik. In cycle of frequency of ketuntasan categoried tidak tuntas and of the name some timeÂ in cycle II categoried as tuntas.The conclusion is applying of SQ3R can improve reading comprehension ability of fourt grade student of SDN Mapala Kec Rappocini Makassar